CORRELATION BETWEEN FETAL BIOMETRY AND FETAL TRANSVERSE CEREBELLAR DIAMETER IN DETERMINATION OF GESTATIONAL AGE FROM THE 15TH WEEK OF GESTATION TO TERM IN HEALTHY WOMEN WITH UNCOMPLICATED PREGNANCY - KAUR, AMANJEET; KUMARI, AMITA; SUMAN, YADAV; PARASDEEP, KAUR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The present study was conducted as an attempt to determine a correlation between the transverse cerebellar diameter (TCD) and the gestational age (GA) as determined by the last menstrual period (LMP) and other sonographic parameters such as biparietal diameter (BPD), head circumference (HC), abdominal circumference (AC), and femur length (FL) in healthy women with uncomplicated pregnancy between the 15th week of gestation to term, to derive normogram for estimating the GA of the fetus from ultrasonographically measured transverse cerebellar diameter. Methods: This prospective study was conducted on 1040 healthy women with uncomplicated pregnancy between the 15th week of gestation to term. Correlation between the GA by LMP with GA by other ultrasound parameters was done using Karl Pearson’s correlation(r). Results: This study demonstrated that throughout 15–40 weeks, TCD showed a strong correlation with clinical GA with a correlation coefficient (r) of 0.967 and a statistically significant correlation. Correlation coefficients between TCD and BPD, TCD and HC, TCD and AC, and TCD and FL being 0.987, 0.987, 0.986, and 0.988, respectively, indicated statistically significant and very strong correlation. Normogram of TCD showed that there was a linear relationship between cerebellar growth and gestational age. Conclusion: TCD can be used as a reliable parameter for the determination of GA.